2009
DOI: 10.1002/jcb.22234
|View full text |Cite
|
Sign up to set email alerts
|

Matrin 3: Chromosomal distribution and protein interactions

Abstract: Matrin 3 (matr3), an abundant protein of the internal nuclear matrix, has been linked to a variety of functional events. As a step toward defining its multifunctional nature, we have studied the association of matr3 with chromosome territories and identified potential interacting proteins. A similar staining pattern of matr3 was observed in fixed WI38 fibroblast cells and in live HeLa cells using a matr3-GFP construct. Matr3 was detected throughout autosomal and the active X chromosome territories. Conversely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 53 publications
4
81
0
Order By: Relevance
“…Using the iCLIP assay, we have found that SAFB1 binds to several lncRNA transcripts (MALAT1, NEAT1, TUG1 and XIST), which have been linked to regulation of gene expression [43]. Both MALAT1 and NEAT1 have been found to associate with genes actively transcribing pre-mRNAs, predominantly around transcription termination sites [52,53], while TUG1, together with MALAT1, is involved in determining PRC2 function [54]. The silencing of an entire X chromosome during female development is orchestrated by XIST, which coats the inactive chromosome.…”
Section: Binding To Non-coding Rnamentioning
confidence: 99%
See 3 more Smart Citations
“…Using the iCLIP assay, we have found that SAFB1 binds to several lncRNA transcripts (MALAT1, NEAT1, TUG1 and XIST), which have been linked to regulation of gene expression [43]. Both MALAT1 and NEAT1 have been found to associate with genes actively transcribing pre-mRNAs, predominantly around transcription termination sites [52,53], while TUG1, together with MALAT1, is involved in determining PRC2 function [54]. The silencing of an entire X chromosome during female development is orchestrated by XIST, which coats the inactive chromosome.…”
Section: Binding To Non-coding Rnamentioning
confidence: 99%
“…Conversely, weaker interactions may be maintained in the presence of low salt, but there may be a risk of artefactual interactions. [10], hnRNPC [10], hnRNPD [120], hnRNPG [25,84,121], hnRNPI [10], hnRNPK [10,122], hnRNPU [10] SR proteins SRSF1 [33], SRSF7 [26], SRSF9 [26,33], SREK1 [88], SRRM1 [123] SR protein kinase SRPK1 [89] Chromatin CHD1 [72], NCOR [37,71], HDAC3, [37,71] BRG1 [73], Matrin3 [54] Transcription RNAPolII [33], TAF II 68 [124], steroid receptors [67][68][69], P53 [70] Miscellaneous PIAS1 [37], ZO-2 [125], Zbed4 [126] Also, co-immunoprecipitation does not distinguish between direct protein interactions and interactions mediated by 'bridging' molecules, such as other proteins or nucleic acids. Formation of homo-and hetero-dimers of SAFB1 and SAFB2, as well as interactions with several hnRNP proteins, has been observed (see Table 1 for a summary of some of the proteins shown to interact with SAFB proteins).…”
Section: Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Matrin 3, an abundant protein of the internal nuclear matrix, has been linked to a variety of functional events. Zeitz et al have reported that matrin 3 interacts with 33 unique nuclear localized proteins and also revealed its propensity for self-association [23].…”
Section: Discussionmentioning
confidence: 99%